2015
DOI: 10.22621/cfn.v129i1.1671
|View full text |Cite
|
Sign up to set email alerts
|

Mass mortality of Northern Map Turtles (<em>Graptemys geographica</em>)

Abstract: We report a mass mortality of Northern Map Turtles (Graptemys geographica [LeSueur, 1817]) on the north shore of Lake Erie, Ontario, Canada. Thirty-five dead adult females were recovered from a nesting area over a period of four weeks. Predation and boat strikes were both excluded as potential cause of death, but the actual cause could not be determined because of the poor condition of the carcasses. Other possible explanations for the mortality include poisoning, drowning, and infection with an unidentified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In some cases, the causes are mysterious (Sheppard , Catrysse et al. ). Many ecologists and conservationists believe that turtles are likely to have only a weak ability to compensate for perturbations and that recovery of turtle populations after declines will be extremely slow, if they occur at all (Brooks et al.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the causes are mysterious (Sheppard , Catrysse et al. ). Many ecologists and conservationists believe that turtles are likely to have only a weak ability to compensate for perturbations and that recovery of turtle populations after declines will be extremely slow, if they occur at all (Brooks et al.…”
Section: Introductionmentioning
confidence: 99%
“…We also evaluated the effect of an event that temporarily increased adult mortality (e.g., poaching, winterkill, catastrophic environmental event) in the population after 30 years by decreasing adult survival rates for the first 2 years in our model by 1%, 10%, and 25%. We selected these morality rates and this timeframe because estimates of map turtle mortality due to poaching are limited but winterkills of northern map turtles can kill nearly 10% of known nesting females in a single season (Catrysse et al 2015) and catastrophic oil spill events can decrease the number of females in a single population by nearly 25% in the first few years following the spill (Otten et al 2022). Thus, rare and isolated events can have substantial influences on population trends for decades following the event itself.…”
Section: Elasticity and Sensitivity Analysismentioning
confidence: 99%
“…Fishing nets set near such communal sites could result in even higher by-catch and mortality. Catrysse et al (2015) reported that during a four-week period the bodies of 35 adult females were found stranded on the north shore of Lake Erie in Ontario. Although the cause of mortality could not be determined, fisheries by-catch could not be excluded as a potential cause.…”
Section: 8mentioning
confidence: 99%